(untitled) (Global Journal of Science Frontier Research, 2017)
In this paper, we introduce a new distribution called transmuted inverted Weibull distribution (TIWD).The new distribution was used in analyzing bathtub failure rates lifetime data.We consider the standard transmuted inverted Weibull distribution (TIWD) that generalizes the standard inverted Weibull distribution (IWD), the new distribution has two shape parameters. The moments, median, survival function, hazard function, maximum likelihood estimators, leastsquares estimators, fisher information matrix and asymptotic confidence intervals were obtained. A real data set is analyzed and it is observed that the (TIWD) distribution can provide a better fitting than (IWD) distribution.